Conductivity of platinum silicide films formed with application of rapid thermal treatment - Anishchik, Victor M.; Harushka, Valiantsina A.; Pilipenka, Uladzimir A.; Ponariadov, Vladimir V.; Saladukha, Vitali A. (Journal of the Belarusian State University. Physics, 2019)
This paper presents the results obtained in studies of variations in resistivity of Pt – Si system in the process of the platinum silicide film formation by the diffusion synthesis method with the use of rapid thermal treatment when tempe-rature varies over a wide range (200 –550 °С). Films 35 nm thick were deposited on monocrystalline silicon substrates by magnetron sputtering of the platinum target using cryopumping down to the pressure no less than  5 × 10–5 Pa in the atmosphere of pure argon. Rapid thermal treatment consisted in irradiation of the unload side of a plate with an incoherent luminous flux in the nitrogen atmosphere. It was found that at temperatures from 200 to 300 °С resistivity of the film is growing due to the Pt2Si phase formation. An increases of temperature up to 350 °С results in lowering of resistivity attri-buted to the formation of a film comprising two phases of platinum silicide: Pt2Si and PtSi, whereas in the case of thermal treatment at 450 °С one can observe an increase in resistivity corresponding to that of a film containing a single phase of platinum silicide – PtSi. Further increase of temperature up to 550 °C had no effect on the resistivity value pointing to the fact that the formation of platinum monosilicide was completed at 450 °С. It is demonstrated that variations in resistivity of platinum films on silicon in the case of thermal treatment at temperatures from 200 to 400 °С are due to the action of d-electrons of this metal during the formation of the high-resistance phase Pt2Si (ρ = 35.2 mW × cm). The formation of the low-resistance phase PtSi (ρ = 28.0 mW × cm) at Т ≥ 450 °С is associated with variations in resistivity both due to metal d-electrons and silicon s- and р-electrons.
Keywords: rapid thermal treatment; platinum silicide; specific resistance; solid phase synthesis